The Frozen Food Made from Fish and Shrimp for the Economic Development of Dayah Darul Faizin Al-Amiriyah - Wirdah Irawati; Yurnalis Yurnalis; Nurhalis Nurhalis (STIE Jambatan Bulan, 2024)
Dayah Darul Faizin is one of the Dayah in Aceh Besar, which has been operating since 2010. Located in Kuta Cot Gle District Village, Aceh Besar Regency. There are 120 students at Dayah Darul Faizin, consisting of 40 men and 80 women. In this area community service is carried out. This service aims to answer the needs of partners, namely Dayah students, in honing their skills in processing marine products in the form of fish and shrimp into various healthy ready-to-eat foods in the form of frozen food for the development of the Dayah economy in the future. The existence of training is also able to be a solution for developing the potential of students in the fields of food security, nutritional fulfillment and entrepreneurship. The service team formulated a 5-day training program by inviting instructors to train and accompany the students in an effort to develop their interests and talents and also train frozen food processing skills. A total of 15 Santri were selected to be training participants in this activity. The main ingredients in making frozen food are Marlin fish (Macaira Indica) and giant prawns. The choice of fish and shrimp ingredients is because they are very easy to obtain in the market, the price is affordable, and they utilize local potential sources. Processed products are stored in the refrigerator freezer and used as frozen food. The practice of training in processing snack foods made from shrimp and fish is easy to apply and has economic advantages to be developed in the future either for family nutritional needs or to be developed into a commercial economic business because there is always market space available for products like this. It is hoped that this practical snack food processing activity will be the beginning of the formation of Dayah Preneurship.